A Survey Regarding Drug Shortage in Tertiary Care Hospitals of Karachi, Pakistan - Fatima, Syeda Aijaz; Khaliq, Asif (Journal of Pharmacy Practice and Community Medicine)
Background: Drug shortages have become a big concering issue for all over the world and for health care providers. The shortage of drugs have adverse and drastic effect on patient care and prescribing practices. Objectives: This aim of this study to assess the current drug shortage problems and adverse effect in of tertiary care hospitals of Karachi. Methodology: This was a cross sectional study in which data collected from different sources: Physicians and Pharmacist by using purposive sampling technique from October 2016 to March 2017. A total of 472 physician and pharmacist had participated in this study and the data was analysed by SPSS. Result: The shortage of injectable dosage form of drug is more common, that accounts for 52.2 % shortage. The main cause of drugs shortage is to increase drugs price which was rated by more than 36% participants.The adverse outcomes due to drugs shortage patient face are length of stay (25%) and cost of treatment (14%) increases reported by respondents. Conclusion: Those physicians and pharmacist who are working in public and private hospital sectors have to face drugs shortage problems. The shortage of drugs happen due to various causes and healthcare staff have to bear several challenges furthermore, all of these in the end make negative consequences on patient health.
Keywords: Health; Patient; Emergency; Drug shortages; Pakistan